"Normative Convergence and Divergence: A Comparison of Digital Cyberbullying Evidence Laws between Indonesia and Singapore in the Digital Era" - Cheza Kania risky; Dewi Mutiah (KRTHA BHAYANGKARA, 2025)
This research examines the validity of digital evidence in cyberbullying cases through a comparative normative legal study between Indonesia and Singapore. Cyberbullying, as a troubling form of cyber violence, leaves a significant digital footprint, making it key evidence in legal proceedings. This study aims to compare the legal frameworks, validity standards, and verification methods for digital proof related to cyberbullying in the two countries, as well as their legal implications for ensuring legal certainty and protecting victims. The research method used is normative law, by analyzing laws and regulations such as the KUHAP and ITE Law in Indonesia, and the Evidence Act in Singapore, along with related jurisprudence and legal doctrine. The results show significant differences in the legal framework of digital evidence. Singapore, with its Evidence Act, has a more explicit and structured legal framework that emphasizes the reliability of digital evidence, providing higher legal certainty. Indonesia, while recognizing digital evidence through the interpretation of "Surat" in KUHAP and the ITE Law, has a more general and flexible legal norm, with potential challenges in verification and legal certainty. This research concludes that Singapore's more advanced legal framework can serve as a reference supports the advancement of Indonesia's legislation pertaining to digital evidence, especially in light of efficiently addressing cyberbullying. This research contributes to the.